BIOLOGI PERBUNGAAN TANAMAN AVOKAD (PERSEA AMERICANA MILL.) - SUKAMTO, L. AGUS (Research Center for Biology-Indonesian Institute of Sciences, 1985)
L. AGUS SUKAMTO 1985.The flowering biology of avocado (Persea americana Mill.). Berita Biologi 3 (1) 8 - H.- A study on the flowering biology of avocado available at Bogor Botanic Garden was made.The observation was conducted in respects to the opening and closing of the flowers, the versality of the pollen grains which are then related to the fruit production.The climatic condition as well as pollination agents which may affect on the vertilization in avocado are also discussed.